Cone Procedure, A New Approach, A New Hope for Ebstein Anomaly Patient: A Case Report - Hidayat, Jefferson; Kurnia, Andri (Proceedings Book of International Conference and Exhibition on The Indonesian Medical Education Research Institute, 2023)
Ebstein anomaly is a rare congenital disease affecting the cardiac structure involving the tricuspid valve, leading to right ventricular dysfunction. Patients with Ebstein’s anomaly may have other structural abnormalities. Asymptomatic patients can be treated with conservative management, while symptomatic patients presenting with severe tricuspid regurgitation, NYHA class III-IV symptoms, and overwhelming tachyarrhythmias should undergo surgery. A 13-year-old girl presented with EA and ASD underwent a cone procedure with direct ASD closure and PFO creation. Cone procedure is a relatively new surgical approach in EA management and is preferred because it can be applied to various anatomical differences in EA. Managing the hemodynamic effects and anesthetic consideration during EA repair can be complex due to right ventricular dysfunction secondary to tricuspid regurgitation (TR). While opening the pericardium, the monitor showed VT, and the patient was given an internal defibrillation. Transesophageal echocardiography (TEE) was done intraoperatively to help evaluate ventricular function. The sternal closure was delayed due to cardiac edema. The procedure was done, but the patient’s hemodynamic was unstable, so it was decided to delay the sternal closure. Many studies showed that the Cone procedure is a long-lasting repair of TR and creates significant functional improvement, resulting in low in-hospital mortality. TEE during the cone procedure has a vital role in evaluating the tricuspid valve’s function after repair. Our patient's cone procedure was successfully done with reduced TR and good biventricular function, as shown in previous studies.